Effects of age, Gender and Allergen Type on Immunoglobulin E Level in Asthma and Allergic Rhinitis Patients - Ahmed, Marwa Baker; Ad’hiah, Ali Hussein (Iraqi Journal of Science, 2022)
This study aimed to determine the effects of age, gender, and allergen type on serum immunoglobulin E (IgE) levels in asthma (AS) and allergic rhinitis (AR) patients. Sixty AS patients, 52 AR patients, and 61 controls were enrolled in the study. Sera of participants were assessed for total IgE level and specific IgE antibody against four allergen types (animal dander, grasses, mites, and molds). The results revealed that median level of total IgE was significantly increased in AS (218.9 IU/mL; p-value < 0.001) and AR (244.3 IU/mL; p-value < 0.001) patients compared to controls (167.1 IU/mL), while, there was no significant difference between AS and AR patients (p-value = 0.270). Logistic regression analysis demonstrated that the increased level of IgE was associated with an increased risk of AS (Odds ratio = 96.93) and AR (Odds ratio = 66.37). Receiver operating characteristic (ROC) curve analysis confirmed the predictive significance of IgE in AS and AR. The estimated area under the curve (AUC) for IgE in AS was 0.889 (p-value < 0.001), and at a cut-off value of 183.7 IU/mL, the sensitivity and specificity were 86.7 and 83.6%, respectively. Almost similar figures were estimated in AR, but the AUC was slightly lower (AUC = 0.873). The IgE level was not influenced by age groups (< 16, 16 – 40, and > 40 years) in AS patients or controls, while, it showed a significantly decreased level in the age group > 40 years of AR patients compared to the corresponding lower age groups (196.3 vs. 252.2 and 264.9 IU/mL, respectively). With respect to gender, the IgE levels showed no significant differences between males and females of patients or controls. For allergen type, mites were the most encountered allergen in age groups and males and females of AS and AR patients, and there were no significant differences between age or gender groups regarding the distribution of seropositive and seronegative patients. Further, the allergen type had no significant influence on the total IgE level. In conclusion, this study indicated the predictive significance of IgE in AS and AR. This significance was not influenced by age, gender, or allergen type.